2004
DOI: 10.1002/nav.20031
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic analysis of a fixed partition policy for the inventory‐routing problem

Abstract: Abstract:We consider the Inventory-Routing Problem (IRP) where n geographically dispersed retailers must be supplied by a central facility. The retailers experience demand for the product at a deterministic rate, and incur holding costs for keeping inventory. Distribution is performed by a fleet of capacitated vehicles. The objective is to minimize the average transportation and inventory costs per unit time over the infinite horizon. We focus on the set of Fixed Partition Policies (FPP). In an FPP, the retail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…With the popularity of vendor-managed inventory (VMI), more and more companies have recognized that significant cost reductions can be achieved by integrating inventory control and vehicle routing into a cost-effective strategy, as illustrated in Chan et al (2002), Kleywegt et al (2002), Anily and Bramel (2004a), Campbell and Savelsbergh (2004), Li et al (2007) and Savelsbergh and Song (2007). Determining such a costeffective distribution strategy is known as Inventory Routing Problem (IRP).…”
Section: Introductionmentioning
confidence: 97%
“…With the popularity of vendor-managed inventory (VMI), more and more companies have recognized that significant cost reductions can be achieved by integrating inventory control and vehicle routing into a cost-effective strategy, as illustrated in Chan et al (2002), Kleywegt et al (2002), Anily and Bramel (2004a), Campbell and Savelsbergh (2004), Li et al (2007) and Savelsbergh and Song (2007). Determining such a costeffective distribution strategy is known as Inventory Routing Problem (IRP).…”
Section: Introductionmentioning
confidence: 97%
“…We can observe that most of the earlier works concentrate on an infinite planning horizon (see for example Aghezzaf et al [9], Anily and Bramel [10] and Campbell and Savelsbergh [11]). …”
Section: Introductionmentioning
confidence: 98%
“…This article revisits a model first analyzed by Chan et al and subsequently by Anily and Bramel . A product has to be distributed from a central warehouse to a set of geographically dispersed retailers with vehicles of limited capacity.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the worst‐case asymptotic ratio between the best FPZIO and the best feasible policy is bounded by 2. Anily and Bramel focused on FP policies and on measuring the worst‐case asymptotic performance of specific FP policies with respect to the best policy of the class. In Anily and Bramel , a lower bound on the cost of the best possible FP policy was derived: it was shown to be asymptotically 98.5%‐effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation